THE EFFECT OF STORAGE CONDITION ON ANTIOXIDANT ACTIVITY OF PROBIOTICS IN YOGURT DRINKS - Silalahi, Jansen; Nadarason, Darshieny; E Silalahi, Yosy C (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to investigate the effect of temperature and time of storage on antioxidant activity of probiotics in yogurt drinks. Methods: The samples used were Yakult, Cimory, YoFit, and BioKul marketed in Medan city. The samples were stored at room and refrigerate temperatures for 2 weeks. Various volumes of samples were withdrawn and mixed with 1 ml of 2,2-diphenyl-1-picrylhydrazil solution and homogenized. Then, it was incubated for 30 min and centrifuged at 5000 rpm for 15 min. The supernatant was collected, and the absorbance was measured at 516 nm by spectrophotometer. The absorbance of different volume of supernatant of each sample was used to construct linear regression equation. Then, the IC50 value was determined. Results: The present study shows that the higher the temperature and the longer the time of storage decreased the antioxidant activity of yogurt drinks. Yakult exhibited the highest antioxidant activity among the analyzed samples. Before storage, the IC50 value of Yakult was 0.2763 ml, and after stored for 2 weeks, the IC50 value of Yakult was 0.3867 ml at refrigerated and 0.5393 ml at room temperature. Conclusions: Probiotic in yogurt drinks stored at refrigerated temperature has higher antioxidant activity than stored at room temperature. The IC50 values of yogurt drinks decreased with storage time. Â